La metodología de Edmundo O’Gorman y su contexto disciplinario - Alejandro Cheirif Wolosky (Nuevo mundo - Mundos Nuevos, 2012)
This article sets out to provide a sketch of Edmundo O’Gorman’s critical methodology and to place it in its vast disciplinary context. The article concludes that the Mexican historian’s method of enquiry resides in its integration of a philosophical conceptual apparatus into the historical method.